2018
DOI: 10.15296/ijwhr.2019.58
|View full text |Cite
|
Sign up to set email alerts
|

The Study of Predictive Value of Uterine Artery Doppler in Incidence of Preeclampsia and Intrauterine Growth Restrictions in Pregnant Women

Abstract: Objectives: Preeclampsia is considered as one of the most important causes of death among pregnant women all around the world. This study aimed to study the predictive value of uterine artery Doppler ultrasonography in the incidence of preeclampsia and the intrauterine growth restriction (IUGR) in pregnant women who attended Fatemieh hospital. Materials and Methods: This study was performed by the prospective cohort method and the statistical population included 108 pregnant women, in their 18-22 weeks of pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 18 publications
4
2
0
Order By: Relevance
“…In this meta-analysis, we found a significant association between the notch presence and SGA and that notch presence was significantly associated with the increased odds of SGA. The similar finding was reported in former studies [ 5 , 13 , 35 ]. Borna et al found that the incidence of SGA in women with notch was significantly greater than women without notch in ultrasonography [ 13 ].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In this meta-analysis, we found a significant association between the notch presence and SGA and that notch presence was significantly associated with the increased odds of SGA. The similar finding was reported in former studies [ 5 , 13 , 35 ]. Borna et al found that the incidence of SGA in women with notch was significantly greater than women without notch in ultrasonography [ 13 ].…”
Section: Discussionsupporting
confidence: 93%
“…In this meta-analysis, we observed higher levels of UtA-PI and UtA-RI in women with SGA compared to those without SGA during the whole pregnancy. Previous studies have reported the similar findings [ 13 , 31 ]. Borna et al performed a study to identify patients at the risk of SGA using UtA, and they observed that mean UtA-PI in women with SGA newborns was significantly higher than those without SGA newborns [ 13 ].…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations